Influencia del carburo de calcio y la granulometría en la lixiviación de oro de un Mineral refractario - Negreiros Vásquez, Henry Daniel (2019)
In this experimental investigation a refractory gold ore from Santiago de Chuco was studied, the chemical composition analyzed was 17.71 g / MT Au and 19% As, which presents refractoriness for gold extraction, with less 16.91% and 33.28% extraction of gold to mesh # 200 and mesh # 400 respectively, for which it was proposed to pretreat grinding with oxidizing reagent of calcium carbide in 3, 6 and 9 Kg / TM and varying the granulometry in P80 = mesh # 200, and P90 = # 400 mesh, followed by agitation leaching using sodium cyanide at 5000 ppm concentration and sodium silicate dispersant. The results obtained are determined by using calcium carbide in low doses and fine granulometry, gold recovery is increased, obtaining the highest gold recovery of 55.52% at 3 Kg / MT of calcium carbide and with granulometry of 90 % through mesh # 400, being the lowest gold recovery of 43.72% at 6 Kg / MT and 80% through the # 200. It is concluded that the dosage of calcium carbide in grinding and regrinding (granulometry) influence the recovery of gold in leaching by agitation with sodium cyanide. It is concluded that at 95% of significance that the dosage of calcium carbide significantly, while the granulometry and the interaction of dosage and granulometry do not significantly influence the recovery of gold from a gold refractory ore with high arsenic content from Santiago de Chuco.